2003
DOI: 10.1242/dev.00365
|View full text |Cite
|
Sign up to set email alerts
|

A Balbiani body and the fusome mediate mitochondrial inheritance duringDrosophilaoogenesis

Abstract: Maternally inherited mitochondria and other cytoplasmic organelles play essential roles supporting the development of early embryos and their germ cells. Using methods that resolve individual organelles, we studied the origin of oocyte and germ plasm-associated mitochondria during Drosophilaoogenesis. Mitochondria partition equally on the spindle during germline stem cell and cystocyte divisions. Subsequently, a fraction of cyst mitochondria and Golgi vesicles associates with the fusome, moves through the ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
307
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(330 citation statements)
references
References 55 publications
12
307
2
4
Order By: Relevance
“…A similar mutant in Caenorhabditis elegans kinesin-1, uncoordinated-116 (unc-116), also did not affect organelle transport (20). To test the ability of this mutant to transport cargoes in the germline, we assayed the distribution of mitochondria, well-known kinesin-1-dependent organelles (3), using a mitochondrial EGFP marker (21). We found that mitochondria were distributed correctly in stage 1-3 egg chambers of Khc mutA oocytes (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…A similar mutant in Caenorhabditis elegans kinesin-1, uncoordinated-116 (unc-116), also did not affect organelle transport (20). To test the ability of this mutant to transport cargoes in the germline, we assayed the distribution of mitochondria, well-known kinesin-1-dependent organelles (3), using a mitochondrial EGFP marker (21). We found that mitochondria were distributed correctly in stage 1-3 egg chambers of Khc mutA oocytes (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The CFP and YFP fluorescence patterns were mitochondrial, and in live egg chambers the signals moved as mitochondria did 26 (data not shown). In nosCIETDY egg chambers, the CFP and YFP signals overlapped completely (Figures 2a, lower egg chamber, and b, white color) when there was no evidence of apoptosis.…”
Section: Detection Of In Vivo Caspase Activitymentioning
confidence: 94%
“…Mitochondria form aggregates with the smooth endoplasmic reticulum (SER), Cummins et al, 1997;Cox and Spradling, 2003;Mitochondrial distribution Wilding et al, 2001Torner et al, 2004;Nishi et al, 2003Mitochondrial movement van Blerkom, 1991Cox and Spradling, 2003;mtDNA content Reynier et al, 2001Spikings et al, 2007mtDNA mutation Yesodi et al, 2002Hsieh et al, 2004Mitochondrial polarity van Blerkom et al, 2003 2007 Function in calcium regulation Machaty et al, 1997;Krisher, 2004;Whitaker, 2008 Mitochondrial dysfunction Tarín, 1996;Eichenlaub-Ritter, 1998;Yin et al, 1998;Ottolenghi et al, 2004;Thouas et al, 2004;Zhang et al, 2006Mitochondria transfer Pinkert et al, 1997Malter and Cohen, 2002;Kong et al, 2004;Yi et al, 2007 a Studies involved in oocytes and embryos and these aggregates are apparently involved in the energy production and deposition before fertilization (Torner et al, 2004). Mammalian oocyte maturation relies not only on a high level of ATP for nuclear envelope breakdown, but also on intracellular calcium, which is derived from the endoplasmic reticulum (ER) and mitochondria (Krisher, 2004).…”
Section: Calcium Signaling In Mitochondriamentioning
confidence: 99%